Persepsi Nasabah Kota Bandung terhadap Implementasi Akad dan Prinsip Bank Syariah Indonesia (BSI) - Sri Andini; Intan; Dika Pratama; Aqiila Nurunnisa Arifin; Desi Mulyani; Fairuz Nasywadhiya Aji; Syarip Hidayat (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2026)
The development of Islamic banking in Indonesia, particularly following the merger of Bank Syariah Indonesia (BSI) in 2021, underscores the importance of evaluating customer perceptions regarding the real implementation of Islamic contracts (akad) and sharia principles. This study aims to analyze the perceptions of active BSI customers in Bandung City toward the implementation of akad and sharia principles, as well as to identify the factors influencing their satisfaction, trust, and loyalty. This study employed a qualitative descriptive method with data collected through open-ended questionnaires distributed to 5 active BSI customers in Bandung City, selected using purposive sampling technique. Primary data were analyzed narratively and supported by secondary data in the form of relevant scientific journal literature. The results indicate that religiosity is the primary motivation for customers in choosing BSI; however, a significant gap exists between this religious enthusiasm and the customers' relatively low level of Islamic contract literacy. Some customers also perceive that Islamic banking practices are not substantially different from conventional banking, triggered by insufficient technical education received. Nevertheless, service quality, ease of digital technology access, and transparency in the profit-sharing system were proven to be key supporting factors for customer satisfaction and loyalty. This study concludes that BSI needs to strengthen its education and socialization programs on Islamic akad through various accessible media to improve Islamic financial literacy and public trust.